2012
DOI: 10.5754/hge12369
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Mediated Signaling Pathway of Gastric Cancer Apoptosis

Abstract: TM can induce ESR and regulate downstream molecules CHOP up-regulation and Bcl-2 down-regulation which lead to BGC823 apoptosis. This study may provide a new theoretical basis for the pathogenesis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The ER is a central cellular organelle in which transmembrane and secretory proteins are synthesized, folded, and matured [37] . The ultrastructural changes we observed in the ER always accompany "ER stress" [38][39][40] . For example, Hanoch et al [38] reported that dilated ER lumen accompanied the response to ER stress in Trypanosoma brucei.…”
Section: Discussionmentioning
confidence: 79%
“…The ER is a central cellular organelle in which transmembrane and secretory proteins are synthesized, folded, and matured [37] . The ultrastructural changes we observed in the ER always accompany "ER stress" [38][39][40] . For example, Hanoch et al [38] reported that dilated ER lumen accompanied the response to ER stress in Trypanosoma brucei.…”
Section: Discussionmentioning
confidence: 79%
“…Conversely, if the stress exceeds the threshold that GC cells can afford, apoptosis may be initiated. For instance, following treatment with 10 µg/ml tunicamycin for 24 h, GRP78 and CHOP were upregulated whereas Bcl-2 was downregulated in the GC cell line BGC823, ultimately leading to apoptosis (60). Vitamin E succinate (RRR-α-tocopheryl succinate; VES) causes cytological changes typical of apoptosis by increasing ER dilation and cytosolic Ca 2+ concentration.…”
Section: Gc Cell Proliferation Under Hypoxia Stress a Protein Kinasementioning
confidence: 99%
“…CHOP is a significant mediator of apoptosis in ER stress 17. Researchers have found that CHOP deletion protects IOP elevation in glucocorticoid-induced ocular hypertension18 and promotes RGCs19 and β cells20 survival in an optic nerve crush mouse model and diabetic mouse model.…”
mentioning
confidence: 99%